2010
DOI: 10.1186/1743-0003-7-35
|View full text |Cite
|
Sign up to set email alerts
|

The relation between neuromechanical parameters and Ashworth score in stroke patients

Abstract: BackgroundQuantifying increased joint resistance into its contributing factors i.e. stiffness and viscosity ("hypertonia") and stretch reflexes ("hyperreflexia") is important in stroke rehabilitation. Existing clinical tests, such as the Ashworth Score, do not permit discrimination between underlying tissue and reflexive (neural) properties. We propose an instrumented identification paradigm for early and tailor made interventions.MethodsRamp-and-Hold ankle dorsiflexion rotations of various durations were impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 47 publications
4
119
0
1
Order By: Relevance
“…As a consequence, we suggest that the Ashworth score is more reflective of the rigidity of the connective and muscular (active) tissue [64] than it is of the reflexive component of spasticity [63]. This seems to be confirmed by the stiffness measurements taken toward the end of the training, when reflexes are more easily controlled.…”
Section: Relationship Between Upper Limb Impedance and Clinical Evmentioning
confidence: 53%
“…As a consequence, we suggest that the Ashworth score is more reflective of the rigidity of the connective and muscular (active) tissue [64] than it is of the reflexive component of spasticity [63]. This seems to be confirmed by the stiffness measurements taken toward the end of the training, when reflexes are more easily controlled.…”
Section: Relationship Between Upper Limb Impedance and Clinical Evmentioning
confidence: 53%
“…[1] Introduction and aim: The intrinsic kinematics of the foot are of interest for a number of clinical conditions, and this is reflected in the large number of multi-segment foot models for gait analysis reported in the literature [1]. These models tend to be based on skin mounted motion capture marker sets, however studies using bone pins have demonstrated significant differences between the true motion of the foot bones and the motion measured using skin mounted markers [2]. This is primarily due to movement of the underlying bony landmarks relative to the surrounding soft tissue.…”
mentioning
confidence: 99%
“…Muscular atrophy and muscle phenotype shift to fast-twitch fiber proportions in the hemiparetic leg muscle after a stroke and relate to muscle fatigue, poor fitness, poor physical performance, and neurologic gait deficit (HaferMacko et al, 2008). Spasticity (hyperactivity of stretch reflexes) and hypertonia (i.e., increased stiffness and viscosity) are common impairments after stroke (de Vlugt et al, 2010;Katz & Rymer, 1989). Spasticity is attributed to increased muscle tone related to hyperreflexia according to Lance (1980) who defined spasticity as a velocity-dependent increase in tonic stretch reflexes (muscle tone) with exaggerated tendon jerks, resulting from reflex hyperexcitability (Lance, 1980).…”
Section: Skeletal Muscle Changes After Hemiparetic Strokementioning
confidence: 99%
“… not standardizing stretch velocity in manual testing (de Vlugt et al, 2010),  not quantifying resistance in absolute units (Pandyan et al, 1999),  not providing an assessment of activated muscle tone (Sommerfeld et al, 2004),  subjectively grading and clustering of scores (Katz & Rymer, 1989;Pandyan et al, 1999),  only being applicable for the extremities (Leonard et al, 2001),  lacking sensitivity for detecting smaller degrees of changes in spasticity (Lance, 1980),  poor discrimination between increased muscle tone and soft-tissue stiffness (de Vlugt et al, 2010;Sheean & McGuire, 2009), and  lacking correlation with functional changes after treatment (Ward, 2000).…”
Section: Common Clinical Measure Of Muscle Tonementioning
confidence: 99%